Education Efforts to Increase Knowledge About Hypertension And Hypotension in Masawah Village Communities, Cimerak Sub-District, Pangandaran District - Putra, Fadlan Gunawan; Nurhayat, Firman Arif; Agapa, M. Fasya Febri; Fauzi, Muhamad Hasman; Fauziah, Mustika; Urrohman, Nida; Anggraeni, Putri Siti; Septiani, Resty; Khoeryza, Rima; Sari, Risna Purnama; Widiawaty, Shindy Cantika; Ulfa, Siti Maria; Amelia, Windi; Mahendra, Yusril Ihza; Saputra, Jumadil; Pratiwi, Anggia Suci; Hendrawan, Budi; Mujiarto, Mujiarto (AbdimasMu UMTAS, 2024)
Blood pressure is an essential factor in the circulatory system. Not all blood pressure in the objects is within normal limits, so it leads to disorders of blood pressure, hypertension and hypotension. Hypertension is a symptom in which abnormal pressure is high in the arteries, causing increased risk of stroke, aneurysm, heart failure, heart attack and kidney damage. Hypotence is a state where blood pressure drops below normal Numbers, which is a low of 90/60 MMHG. According to information from the elderly poshaandu in the village of Masawah, hypertension is the highest disease in the village of Masawah, especially in the elderly. On the other hand, hypotency is lower than hypertensive. The public’s performance of devoted activity is carried out in the village of Masawah, the cipeacock district. This public devotion was carried out from August 8 to September 8, 2022.  The object of this devotion was the rural community of Masawah especially the elderly. The purpose of this society’s devotion is to increase public knowledge about things related to hypertension and hypotension. The dedicated method of learning about hypertension and hypotension by including advanced village, community and cultural and cultural tools. Implement by direct examination of blood pressure, the transmission of materials for hypertension and hypotension, and explained that the majority of diseases that people suffer in the village of Masawah are hypertensive. Results from such educational activities promote public awareness of health care. In light of this educational activity, people have become better at understanding about things related to hypertension as well as hypotension and society can implement their daily knowledge by abstaining from all things that cause rise and fall in blood pressure